GPI- Anchored Proteomes and Their Biochemical Pathway in Alveolates: Evolutionary Insights and Heterologous Expression in Tetrahymena Thermophila - Puca, Gervasio; Montes, Maria G.; Orlowski, Juan; Tomazic, Mariela Luján; Gonzalez Maglio, Daniel H.; de la Fuente, Carolina; Florin-Christensen, Mónica; Schnittger, Leonhard; Nusblat, Alejandro D. (Wiley, 2025)
Glycosylphosphatidylinositol (GPI)-anchored proteins (GPI-APs) play essential roles in eukaryotic cell biology, yet their evolutionary diversity across alveolates remains poorly understood. Here, we conducted a comparative genomic analysis of GPI biosynthetic pathways and GPI-AP repertoires across representative species of Ciliophora, Apicomplexa, and Dinoflagellata. Our findings reveal lineage-specific patterns of gene loss, expansion, and functional divergence, with ciliates exhibiting reduced canonical enzyme sets but expanded trafficking components. Using a benchmarked pipeline of GPI-AP predictors combined with signal peptide detection, we identified candidate GPI-anchored proteins and performed functional annotation to determine enriched Gene Ontology terms. To complement the bioinformatic analyses, we expressed the apicomplexan GPI-anchored antigen GPI4 from Babesia bovis in Tetrahymena thermophila. This approach extends previous efforts that used Tetrahymena as a heterologous expression system for parasite surface antigens. The recombinant protein localized to ciliary membranes and showed features consistent with proper processing. This study highlights the evolutionary plasticity of GPI systems in alveolates and reinforces the utility of Tetrahymena as a eukaryotic platform for the production and analysis of GPI-anchored proteins with potential diagnostic or immunoprophylactic applications.